Accelerated landing in a stingless bee and its unexpected benefits for traffic congestion. Issue 1921 (26th February 2020) - Tichit, Pierre; Alves-dos-Santos, Isabel; Dacke, Marie; Baird, Emily
Abstract : To land, flying animals must simultaneously reduce speed and control their path to the target. While the control of approach speed has been studied in many different animals, little is known about the effect of target size on landing, particularly for small targets that require precise trajectory control. To begin to explore this, we recorded the stingless bees Scaptotrigona depilis landing on their natural hive entrance—a narrow wax tube built by the bees themselves. Rather than decelerating before touchdown as most animals do, S. depilis accelerates in preparation for its high precision landings on the narrow tube of wax. A simulation of traffic at the hive suggests that this counterintuitive landing strategy could confer a collective advantage to the colony by minimizing the risk of mid-air collisions and thus of traffic congestion. If the simulated size of the hive entrance increases and if traffic intensity decreases relative to the measured real-world values, 'accelerated landing' ceases to provide a clear benefit, suggesting that it is only a useful strategy when target cross-section is small and landing traffic is high. We discuss this strategy in the context of S. depilis ' ecology and propose that it is an adaptive behaviour that benefits foraging and nest defence.